Sounding Black or White: priming identity and biracial speech. - Gaither, Sarah E.; Cohen-Goldberg, Ariel M.; Gidney, Calvin L.; Maddox, Keith B. (Tufts University. Tisch Library., 2019)
Research has shown that priming one's racial identity can alter a biracial individuals' social behavior, but can such priming also influence their speech? Language is often used as a marker of one's social group membership and studies have shown that social context can affect the style of language that a person chooses to use, but this work has yet to be extended to the biracial population. Audio clips were extracted from a previous study involving biracial Black/White participants who had either their Black or White racial identity primed. Condition-blind coders rated Black-primed biracial participants as sounding significantly more Black and White-primed biracial participants as sounding significantly more White, both when listening to whole (Study 1a) and thin-sliced (Study 1b) clips. Further linguistic analyses (Studies 2a-c) were inconclusive regarding the features that differed between the two groups. Future directions regarding the need to investigate the intersections between social identity priming and language behavior with a biracial lens are discussed.